2013
DOI: 10.1007/s10393-013-0842-6
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Antimicrobial Resistance in Bacteria Isolated from Stranded Marine Mammals of the Northwest Atlantic

Abstract: Studies on marine mammals can inform our understanding of the environmental health of the ocean. To evaluate the potential for changes in antimicrobial resistance, we analyzed a database spanning 2004-2010 that consisted of bacterial isolate identity and antimicrobial sensitivity for stranded pinnipeds in the Northwest Atlantic. Samples (n = 170) from treated animals yielded 310 bacterial isolates representing 24 taxa. We evaluated changes in antimicrobial class resistance from 2004 to 2010 for eight taxa. Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Enterobacteriaceae are frequently found in the gut flora of reptiles [39,40]. Previously known as commensal bacteria, today Enterobacteriaceae are considered as cause of serious illness worldwide, mainly in immunocompromised patients [41], and suggested as potential secondary invaders of infections in marine animals [42]. Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae are frequently found in the gut flora of reptiles [39,40]. Previously known as commensal bacteria, today Enterobacteriaceae are considered as cause of serious illness worldwide, mainly in immunocompromised patients [41], and suggested as potential secondary invaders of infections in marine animals [42]. Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…) and that AMRB prevalence has been alarmingly increasing over the last decade (Wallace et al . ). Furthermore, with the global loss of natural wetlands, waterbirds have become increasingly dependent on alternative and artificial habitats including wastewater treatment wetlands (Murray & Hamilton ), which could favour the transmission to wild birds of AMRB of human origin.…”
Section: Habitats: Where Is the Resistance?mentioning
confidence: 97%
“…As discussed in part II, water seems to play a major role in the dispersal of antibiotics and AMRB to natural ecosystems. As an illustration of this role, studies carried out on marine mammals to date have shown that they carry highly diverse AMRB (Schaefer et al 2009) and that AMRB prevalence has been alarmingly increasing over the last decade (Wallace et al 2013). Furthermore, with the global loss of natural wetlands, waterbirds have become increasingly dependent on alternative and artificial habitats including wastewater treatment wetlands (Murray & Hamilton 2010), which could favour the transmission to wild birds of AMRB of human origin.…”
Section: Habitats: Where Is the Resistance?mentioning
confidence: 99%
“…Thus, in both marine and terrestrial environments, wildlife can come into direct contact with most antibiotics, even at sub-inhibitory concentrations [10], leading to the selection of antibiotic-resistant microbiota. In this context, wildlife represents a potential reservoir, or vector, of resistant pathogens and ARGs [1,11,12]; therefore, in the study of the spread of the AMR, it may be useful to evaluate the role of migratory wildlife species, which can carry a resistant microbiota.…”
Section: Introductionmentioning
confidence: 99%